Radiojornalismo na cibercultura: por uma nova experiência de rádio em tempos de redes sociais e hipermobilidade - Prado, Magaly Parreira do (2012)
This Thesis focuses on a study of radio journalism produced by users of mobile devices, within the sphere of hybridization evoked in cyberculture. The first part discusses the articulation of the technological potential associated with audio technology, starting from an examination of mobile media based on social networks as determinants of new forms of communication in conditions of hypermobility. The second part puts forward the main hypothesis that users who access the web via mobile phone may become the primary audience for a new radio station. The main research problem consists in determining the operational relevance of a radio station designed according to the emerging characteristics and potentialities of cyberculture. To what extent can one expect the creation of a radio station along these lines, considering that, for this Thesis, the empirical research involved an investigation of a possible radio station that proposes elements not yet employed socially on a regular basis? Who could contribute to this type of differentiated programming? Would users participate with urban notes about their daily routine? Could this information from the audience produce knowledge? These questions will be answered in the discussion and description about the experiments that were developed to underpin the argumentation of this thesis. The epistemological and theoretical framework links communication, culture and speed with authors who evaluate communication in real time. The theoreticians consulted here range from Marshall McLuhan and Armand Balsebre to Manuel Castells and Néstor Garcia Canclini. Some of the authors who analyze mobile media, such as Lucia Santaella and André Lemos, helped shed light on the themes of this research, together with authors who offer critiques about communication in cyberspace and expand on the concepts examined here, such as Paul Virilio and Eugênio Trivinho. The methodology adopted here comprised the performance, analysis and circumstantiated report of research experiments in web and radio journalism produced with mobile devices, which consisted of geolocalization and street mapping of São Paulo, chatting and streaming, and broadcasting through social networks. The third part of this thesis describes the website used for the experiments. As a result, we hope that reflection about communication in high-speed times has established the fundamental precepts for audiocast programming, combining microcontent linked with notes about places in order to offer passers-by enhanced information about the mapped surroundings via mobile phone. As an experiment, because it considered market routines from a different angle, the demonstration of an innovative radio was, in itself, a criticism of traditional radio broadcasting, and is expected to make a scientific contribution to the ongoing history of radio broadcasting